Perfil das famílias tomadoras de crédito no Brasil: caracterização a partir de um modelo desenvolvido com microdados da POF 2008/09 - Mendonça, Danilo Marques de (2014)
After the period of monetary stabilization started with the Real Plan in 1994 , the credit market has shown annual growth rates of 20 %. About 40 % of this growth came from the credit market for individuals . This paper analyzed the profile of the families who have credit expenses, and what changes in their characteristics can cause any effect in their propensity to take credit . For this purpose we applied binary logit choice model based on microdata from the Household Budget Survey (POF 2008 / 09 ) of the IBGE, in an attempt to measure the probability of the family take a loan. For this, we used categorical variables relating to the constitution of families, such as education level, sex, race and age of household head, and other information on the composition of household expenditures found in POF. The data suggest that the two most important factors to increase the likelihood of family borrowing is the age of the household head and income per capita. However other factors also contribute significantly, such as the existence of financial investment spending , expend with reform the household or even health spending, children's age, sex, race and education of household head